Mixed‐Methods Approaches in Special Education Research. Issue 4 (28th December 2022) - Love, Hailey R.; Cook, Bryan G.; Cook, Lysandra
Abstract: Mixed‐methods research can uniquely inform special education practice by combining qualitative and quantitative research approaches. However, its distinct features can also make mixed‐methods research difficult to understand and apply. In this article, we provide an introduction to mixed‐methods research purposes, designs, and quality considerations to help practitioners critically consume and apply this type of research when working with students with learning disabilities and their families. We describe three sample research studies to illustrate mixed‐methods designs and contributions. Our take‐home message is that mixed‐methods research (a) requires unique research practices to meaningfully combine qualitative and quantitative research approaches in a single study and (b) can be particularly useful for informing special education practice in real‐world contexts.